Effects of different crumb rubber sizes on the flowability and compressive strength of hybrid fibre reinforced ECC - Khed, V.C. (Institute of Physics Publishing, 2018)
The different sizes of crumb rubber have been used to investigate the effects on flowability and the compressive strength of the hybrid fibre reinforced engineered cementitious composite. Two sizes of crumb rubber 30 mesh and 1 to 3mm were used in partial replacement with the fine aggregate up to 60. The experimental study was carried out through mathematical and statistical analysis by response surface methodology (RSM) using the Design Expert software. The response models have been developed and the results were validated by analysis of variance (ANOVA). It was found that finer sized crumb rubber inclusion had produced better workability and higher compressive strength when compared to the larger size and it was concluded that crumb rubber has negative effect on compressive strength and positive effect on workability. The optimization results are found to an approximately good agreement with the experimental results. Â© 2018 Published under licence by IOP Publishing Ltd.